The potential of exosomes in regenerative medicine and in the diagnosis and therapies of neurodegenerative diseases and cancer - Odehnalová, Nikola; Šandriková, Viera; Hromadka, Róbert; Skaličková, Markéta; Dytrych, Petr; Hoskovec, David; Kejík, Zdeněk; Hajduch, Jan; Vellieux, Frédéric; Vašáková, Martina Koziar; Martásek, Pavel; Jakubek, Milan (Frontiers in Medicine, 2025)
Exosomes, nanosized extracellular vesicles released by various cell types, are intensively studied for the diagnosis and treatment of cancer and neurodegenerative diseases, and they also display high usability in regenerative medicine. Emphasizing their diagnostic potential, exosomes serve as carriers of disease-specific biomarkers, enabling non-invasive early detection and personalized medicine. The cargo loading of exosomes with therapeutic agents presents an innovative strategy for targeted drug delivery, minimizing off-target effects and optimizing therapeutic interventions. In regenerative medicine, exosomes play a crucial role in intercellular communication, facilitating tissue regeneration through the transmission of bioactive molecules. While acknowledging existing challenges in standardization and scalability, ongoing research efforts aim to refine methodologies and address regulatory considerations. In summary, this review underscores the transformative potential of exosomes in reshaping the landscape of medical interventions, with a particular emphasis on cancer, neurodegenerative diseases, and regenerative medicine.